Desain Rencana Pelaksanaan Pembelajaran (RPP) Masa Pandemi Covid-19 di TK PKK 93 Karangtengah - Setyaningrum, Helda (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The existence of Covid-19 in Indonesia has caused a bad impact on psychology and human behavior and education, especially in education, namely PAUD education. But now Covid-19 has subsided, so what used to be full of online or online learning has now started with face-to-face learning. With this, learning is now starting to implement limited face-to-face learning so that learning can still run optimally, so teachers must be able to design RPP (Learning Implementation Plans) that are different from the previous RPP. The type of research used is descriptive qualitative which is used to obtain information on the design of face-to-face learning implementation plans during the Covid-19 pandemic. The research subjects or respondents for this study were the principal of the PKK 93 Kindergarten Karangtengah. Data collection techniques in the form of interviews and documentation. The design made by the teacher to carry out limited face-to-face learning is carried out twice a week at school, the rest will be done online through WhatsApp social media. Lesson plan lesson plans adapted to pandemic conditions, implementation of learning with an emphasis on material delivery; assessment/evaluation carried out in accordance with existing conditions and complying with health protocols. Face-to-face learning activities continue normally despite the limited time available in accordance with government regulations. The results of this study will be useful as a reference for PAUD teachers who have designed a limited face-to-face Learning Implementation Plan during the COVID-19 pandemic